PERLINDUNGAN HUKUM TERHADAP ANAK KORBAN BULLYING: DAMPAK DAN UPAYA PENCEGAHAN RISIKO BUNUH DIRI DI INDONESIA - Reny Okprianti; Nur Husni Emilson; Chinta Oktariani; Annisa Qodriyah; Najla Nisrina Prudencie Lindon; Nyayu Nabilla Az-Zahra (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2025)
The issue of bullying among children is becoming a serious concern due to its psychological impact, which can lead to severe mental disorders such as anxiety, depression, and even suicidal thoughts. In Indonesia, despite the existence of the Child Protection Law, the implementation of policies regulating the protection of children from bullying still faces various challenges. This study aims to examine the impact of bullying on children's mental health and identify the legal protection mechanisms available to reduce the risk of suicide due to bullying. This study uses a qualitative approach, with data collection methods through literature studies and document analysis, including data from the Indonesian Child Protection Commission (KPAI) and relevant laws and regulations. The findings show that bullying in Indonesia, whether verbal, physical, social, or cyberbullying, has a significant psychological impact on children, increasing the potential for suicide. This study emphasizes the need to strengthen child protection policies and implement more effective psychological support for victims of bullying. In conclusion, this study makes an important contribution to understanding the relationship between bullying and children's mental health, and encourages the improvement of policies and more robust reporting systems in schools to prevent suicide among children who are victims of bullying.